Perceived Organizational Support and Employee Engagement in Fast Food Service Industry - WAHAB, ETA (Research in Management of Technology and Business, 2022)
Developing employee engagement concept is crucial nowadays which organization has been focused on. An organization has to pay more attention on maintain and enhance the employee engagement for the better performance in the organization. Employees and employers have been found to benefit from perceived organisational support (POS). The aim of the study is determining the level of perceived organizational support and to determine the level of employee engagement. This study also attempts to understand how perceived organizational support could be related to the employee engagement in the fast-food service industry. Quantitative study had been used in this study by distributing questionnaire survey to the respondent that focused on employees at operational level in fast food service industry in Johor Bahru area. A total of 140 questionnaires had been distributed to the respondents with a response rate of 85%. The data collected had been analysed using both descriptive and correlation analysis. The study found that both POS and employee engagement are at the high level. This study also found that there is a positive correlation between perceived organizational support and employee engagement among the employee at operational level in fast-food service industry